A BNCC e as competências do professor e da professora de Educação Física - Manfio, Fabiane Rossato (2024)
The present master thesis has the objective of identifying in the Brazilian Common Curriculum National Bases (BNCC, 2018) the Physical Educational Conception and the competencies that the Physical Education coach/teacher has to follow to materialize the proposition establised in the BNCC in her/his pedagogical practice. In order to do this, the scientific production through bibliographical research was carried out aiming to identify and analyze what has already been produced concerning Physical Education professional practices within a determined slot of time and space. One of the specific objectives was to identify the conception of BNCC and the theoretical/methodological determinants presented in the document, the Physical Education coach/teacher’s competencies in materializing the proposition of the document (BNCC, 2018) from primary level to senior high (12 years of study). In terms of methodological research, Dialectical Historical Materialism was employed, Bibliographical Review was done based on the BNCC and, in particular, an analysis of general and specific competencies of Physical Education. It has been noticed that the conception of Physical Education presented in the BNCC is based on leaners’adaptation to modern society through the acquirements of competencies and abilities that structure the new educational thinking giving sustentability to the process of productive re-arrangement. BNCC establishes Physical Education coaches/teachers’ pedagogical activities according to competencies, establishing a dialogue with the new working conditions. Thus, BNCC establishes a relationship between competencies which leaners have to develop along their school years and the competencies the Physical Education coach/teacher needs to develop in her/his classes. Among specific competencies that Physical Education coaches/teachers need to develop in their classes, one can point out planning and employing strategies to solve challenges, interpreting and re-creating values, meanings and signifiers attributed to different corporal practices, valuing collective work and pointing out selfinvolvement in developing, experimenting and appreciating different corporal practices.